Pirates of Somalia Crime and Deterrence on the High Seas - Do, Quy-Toan (World Bank E-Library Archive, 2016)
Piracy off the coast of Somalia took the world by surprise when, within a six-year span (2005-2011), as many as 1,099 ships were attacked, among which more than 200 were successfully hijacked. In 2012 however, attacks had plummeted with no new hijacking reported between 2013 and mid-2015. The paper quantitatively investigates the roles of two crime deterrence measures widely believed to be responsible for the collapse of Somali piracy: the deployment of international navies in pirate-infested waters and the provision of armed security guards onboard vessels. Using unique data on attacks, hijacks, and ransoms to calibrate a structural model of Somali piracy, the paper estimates the elasticity of crime with respect to deterrence and highlights the positive and negative spillovers generated by the private adoption of onboard armed security. The paper discusses counterfactual scenarios obtained by varying the intensity and composition of deterrence measures